Ecology and management of the invasive lionfish Pterois volitans/miles complex (Perciformes: Scorpaenidae) in Southern Costa Rica - Sandel, Vera (Universidad de Costa Rica, 2015)
Invasive species alter ecosystem integrity and functioning and are considered one of the major threats to biodiversity on a global scale. The indopacific lionfish (Pterois volitans [Linnaeus, 1758] / miles [Bennet, 1882] complex) is the first non-native marine fish that has established itself in the Western Atlantic. It was first reported in Florida in the 1980s and then spread across the entire Caribbean in subsequent years. In Costa Rica, lionfish were first sighted by the end of 2008 and are now present in all South Caribbean reefs. Lionfish are a major problem for local fisherman by displacing native fish species. The aim of this study was to determine population density, size and diet of lionfish populations at four study sites along the Southern Caribbean coast of Costa Rica. Two of the sites were located inside the National Park Cahuita where regular lionfish removal occurs, whereas the other two study sides do not experiment this kind of management. Total length and wet weight of >450 lionfish individuals were determined between March and June 2011. Three relative metrics of prey quantity (percent number, percent frequency, and percent weight) were compared from ~300 lionfish caught with the polespear in shallow waters (<7m depth). Population density was assessed weekly through visual transect surveys. Our results showed that lionfish preyed mostly upon teleosts and crustaceans. Teleosts dominated lionfish diet in percent frequency (71%) and percent weight (85%), whereas crustaceans had the highest percent number (58%). The top five teleost families of dietary importance were Pomacentridae, Acanthuridae, Blennidae, Labridae and Serranidae. The average total length (±SD) of lionfish was 18.7(±5.7)cm and varied significantly between sites (p<0.001). Mean density of lionfish was 92fish/ha with no significant differences between sites.Smallest fish and lowest densities were found at the two sites inside the National Park Cahuita. Despite management efforts on a regional scale, nationwide efforts are ineffective and lionfish control activities are poorly implemented. We conclude that there is an urgent need to develop an improved institutional framework for local lionfish control that promotes effective coordination among the relevant stakeholders in order to deal with invasive lionfish in Costa Rica.